2017
DOI: 10.1002/2327-6924.12480
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of specialist referrals at a rural health care clinic

Abstract: Purpose Transition to a value‐based care system involves reducing costs improving population health and enhancing the patient experience. Many rural hospitals must rely on specialist referrals because of a lack of an internal system of specialists on staff. This evaluation of the existing specialist referrals from primary care was conducted to better understand and improve the referral process and address costs, population health, and the patient experience. Data sources A 6‐month retrospective chart review wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
4
0
2
Order By: Relevance
“…It is very difficult to justify these records. Some studies have also reported a higher rate of unnecessary rural patient PC referrals,[ 11 ] perhaps as a result of the higher use of public and non-hospital based consultations by the rural population,[ 12 13 ] but it also could be due to a lack of communication and/or coordination among PC practitioners. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…It is very difficult to justify these records. Some studies have also reported a higher rate of unnecessary rural patient PC referrals,[ 11 ] perhaps as a result of the higher use of public and non-hospital based consultations by the rural population,[ 12 13 ] but it also could be due to a lack of communication and/or coordination among PC practitioners. [ 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…One or more substances such as enzymes (glucoronidase), 3 alpha, beta and 20 pregnanediol in breast milk although to be possible cause of breast milk jaundice. Jaundice is influenced by several factors, namely dehydration, weight loss after birth, bleeding, cephalohaematoma, contusions, babies in mothers with diabetes, acidosis, apixia, and gastrointestinal obstruction [4].…”
Section: Introductionmentioning
confidence: 99%
“…Em alguns utiliza-se a "população consultadora" do território do serviço de APS, 14 em outros o número de consultas no serviço. 15,16 Alguns estudos 14,15,16,17,18 realizaram uma análise dos padrões desse referenciamento, porém, no que se refere à realidade brasileira, 19 pouco foi explorado (Quadro 1). A oferta de especialistas focais no Sistema Único de Saúde (SUS) é escassa e a alocação de recursos deve ser otimizada.…”
Section: Introductionunclassified